Berkubang dalam Lumpur, Bekerja Bersama Orang Miskin Wajah Keterlibatan Sosial Gereja Ganjuran - Dionius Bismoko Mahamboro (Jurnal Teologi (Journal of Theology), 2014)
The Catholic Church in Asia has declared triple-dialogue (dialogue with the Asian cultures, with religions and with the poor) as its way of being Church. The farmers belong to the poor in most of Asian countries, especially in Indonesia. This article tries to trace back the history of the Asian Churchs concern with the farmers, which are the representation of the poor. This concern has inevitably touched socio-cultural and socio-political dimensions of christian faith, which lead the christian communities to the most concrete social problem of the local communities, and at the same time connect them with global issues like hunger and food industrialization, or ecological crisis and sustainable farming.